Staphylococcal Enterotoxins - Victor E. Reyes; Ellen J. Beswick; Irina V. Pinchuk (Toxins, 2010)
Staphylococcus aureus (S. aureus) is a Gram positive bacterium that is carried by about one third of the general population and is responsible for common and serious diseases. These diseases include food poisoning and toxic shock syndrome, which are caused by exotoxins produced by S. aureus. Of the more than 20 Staphylococcal enterotoxins, SEA and SEB are the best characterized and are also regarded as superantigens because of their ability to bind to class II MHC molecules on antigen presenting cells and stimulate large populations of T cells that share variable regions on the b chain of the T cell receptor. The result of this massive T cell activation is a cytokine bolus leading to an acute toxic shock. These proteins are highly resistant to denaturation, which allows them to remain intact in contaminated food and trigger disease outbreaks. A recognized problem is the emergence of multi-drug resistant strains of S. aureus and these are a concern in the clinical setting as they are a common cause of antibiotic-associated diarrhea in hospitalized patients. In this review, we provide an overview of the current understanding of these proteins.